A systematic mapping on the use of visual data mining to support the conduct of systematic literature reviews - Felizardo, KR; MacDonell, SG; Mendes, E; Maldonado, JC (Academy Publisher, 2012)
A systematic literature review (SLR) is a methodology used to find and aggregate all relevant existing evidence about a specific research question of interest. Important decisions need to be made at several points in the review process, relating to search of the literature, selection of relevant primary studies and use of methods of synthesis. Visualization can support tasks that involve large collections of data, such as the studies collected, evaluated and summarized in an SLR. The objective of this paper is to present the results of a systematic mapping study (SM) conducted to collect and evaluate evidence on the use of a specific visualization technique, visual data mining (VDM), to support the SLR process. We reviewed 20 papers and our results indicate a scarcity of research on the use of VDM to help with conducting SLRs in the software engineering domain. However, most of the studies (16 of the 20 studies included in our mapping) have been conducted in the field of medicine and they revealed that the activities of data extraction and data synthesis, related to conducting the review phase of an SLR process, have more VDM support than other activities. In contrast, according to our SM, previous studies using VDM techniques with SLRs have not employed such techniques during the SLR’s planning and reporting phases.
Keywords: Systematic Mapping; Systematic Literature Review; Visual Data Mining